Analysis for steering feel on steer-by-wire model - Do, Văn Dũng; Nguyen, Văn Bang; Tran, Văn Lợi (Journal of Technical Education Science, 2015)
In recent year, Steer by Wire is a focus interest of automotive researchers. To Because of the separation, there are some problems which must be solved. The first, it must ensure that the motions of upper part (hand-wheel) and lower part have the same speed. The second, it must ensure that Steer by wire has to produce realistic steering feel. The paper focus on how to pro- duce steering feel and testing on Steer by Wire model